A 'Giving way' captured during walking by gyroscopes and plantar force sensors. (2nd December 2021) - Takeda, Ryutaro; Nakajima, Kanako; Anzai, Emi; Tanaka, Sakae; Ohta, Yuji; Matsumoto, Takumi
Abstract: 'Giving way' is a rapid inversion of the rear part of the foot, which does not result in an acute lateral ankle sprain. It is a specific event for patients with chronic ankle instability (CAI). This report described a 'giving way' in an 18-year-old female with CAI, which was biomechanically captured during walking on the flat surface. Shoes with unstable heel having a hemisphere rubber on the sole of the heel were used to provoke 'giving way'. To the authors' knowledge, this is the first report describing the kinetics of 'giving way' during walking. The event of 'giving way' was captured by an Inertial Motor Unit located on the dorsum of the foot and an insole-shaped plantar force measurement device. 'Giving way' provided distinctive data on both kinds of devices. Gyroscope data showed a rapid increase of inversion/plantarflexion/internal rotation (maximum levels: 204/280/346 degree/s) and following eversion/dorsiflexion/external rotation (maximum levels: 509/798/797 degree/s) of the foot segment at 350 ms − 492 ms after the heel strike. Plantar force data demonstrated the rapid decrease and subsequent recovery of the regional force on the head of 1st metatarsal head, suggesting a rapid inversion followed by the foot's defensive eversion. Although the maximum angular velocity of the inversion was smaller and the duration of inversion phase of 'giving way' was shorter than in previous reports, the characteristics of the following eversion phase of 'giving way' were consistent with earlier reports. The eversion must be a more specific phase than the inversion in the kinematics of 'giving way'.